Cyberspace and gay rights in a digital China: queer documentary filmmaking under state censorship - Shaw, Gareth; Zhang, Xiaoling (SAGE Publications, 2017)
Owing to China’s austere censorship regulations on film media, directors of films and documentaries engaging with lesbian, gay, bisexual and transgender themes have struggled to bring their work to domestic attention. Working outside of the state-funded Chinese film industry has become necessary for these directors to commit their narratives to film, but without approval of China’s State Administration of Press, Publication, Radio, Film and Television, these artists have had little chance of achieving widespread domestic distribution of their work. However, advancements in new media technology and Web 2.0, ranging from digital video formats to Internet-based distribution via social media networks and video-hosting platforms, provide opportunities for Chinese audiences to access films and documentaries dealing with LGBT themes. This empirical study assesses how production, promotion and consumption of queer documentary films are influenced by the development of social media within Chinese cyberspace. Through close readings of microblogs from Sina Weibo this study combines analysis of contemporary research with digital social rights activism to illustrate contemporary discourse regarding film-based LGBT representation in China. Finally, the study comments on the role that documentary filmmaking plays in China’s gay rights movement, and discusses the rewards (and challenges) associated with increased levels of visibility within society.